The ALPHA-2 apparatus - facilitating experimentation with trapped antihydrogen - Christopher Baker (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2025)
This paper describes the ALPHA-2 apparatus, used at the CERN Antiproton Decelerator facility for the study of trapped antihydrogen atoms. Details of both the construction and performance are included. Prominence is given to both the new and the improved features, with respect to the original ALPHA assembly, of the apparatus including a stand-alone antiproton catching trap, the traps used to mix antiparticles to produce the anti-atoms, the magnetic atom trap used to hold some of them, and access for laser light to facilitate excitation of the antihydrogen 1-2 and 1-2 transitions.